Scrotal Mass - Farhat Said; El Rassi Patrick (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2014)
A 45-year-old man presented to the emergency room with abdominal pain and distention, dyspnea and a scrotal mass with absence of a visible penis as shown in the figure 1 below. Abdominal circumference was 120 cm, scrotum circumference was 80 cm and the height of the scrotum was 35 cm. There were no signs of acute abdomen and preliminary routine laboratory labs were within normal except for minimally elevated transaminase levels. Physical examination showed that the patient has ascites along with a compressible painful scrotum and he is known to have Hepatitis C. There were no signs of acute gastrointestinal bleeding or encephalopathy.